Stronger effects of simultaneous warming and precipitation increase than the individual factor on soil bacterial community composition and assembly processes in an alpine grassland - Wei, Xiaoting; Han, Bing; Wu, Bo; Shao, Xinqing; Qian, Yongqiang (Frontiers in Microbiology, 2023)
Composition and traits of soil microbial communities that closely related to their ecological functions received extensive attention in the context of climate changes.We investigated the responses of soil bacterial community structure, traits, and functional genes to the individual warming, precipitation increases, and the combination of warming and precipitation increases in an alpine grassland in the Qinghai-Tibet Plateau that is experiencing warming and wetting climate change. Soil properties, plant diversity and biomass were measured, and the ecological processes and environmental factors driving bacterial community changes were further explored.Results indicated that the Shannon diversity of soil bacterial communities decreased significantly only under the combination treatment, which might due to the decreased plant diversity. Soil bacterial community composition was significantly correlated with soil pH, and was affected obviously by the combination treatment. At the taxonomic classification, the relative abundance of Xanthobacteraceae and Beijerinckiaceae increased 127.67% and 107.62%, while the relative abundance of Rubrobacteriaceae and Micromonosporaceae decreased 78.29% and 54.72% under the combination treatment. Functional genes related to nitrogen and phosphorus transformation were enhanced in the combination treatment. Furthermore, weighted mean ribosomal operon copy numbers that positively correlated with plant aboveground biomass increased remarkably in the combination treatment, indicating a trend of life-history strategies shift from oligotrophic to copiotrophic. Stochastic processes dominated soil bacterial community, and the proportion of stochasticity increased under the combination treatment. Our study highlights the significant effects of simultaneous warming and precipitation increase on soil bacterial community.